Apitherapy - the medical use of bee products - Przemysław Szabat; Julita Poleszak; Marta Szabat; Grzegorz Boreński; Magdalena Wójcik; Joanna Milanowska (Kazimierz Wielki University, 2019)
Introduction: Bee products have been used by man for centuries. However, their therapeutic options are not fully understood. Aim of the study: To review research on the possibilities of using the medicinal properties of bee products. Material and method: Standard criteria were used to review literature data. Search for articles in the PubMed database was carried out using the following keywords: apitherapy, honey, bee venom, propolis, royal jelly, bee pollen. Description: Apitherapy is a healing method known to mankind since the oldest times. Due to the diverse composition, substances produced by bees show a number of activities, which include Antioxidant, immunomodulatory, antibacterial and anticancer effect. Thanks to numerous mechanisms, they have a beneficial effect on wound healing, cardiovascular diseases and metabolic disorders. Summary: Numerous properties and a wide range of activity of each bee product brings the possibility of using them in the therapy of many diseases.